A RETROSPECTIVE STUDY OF OBSTRUCTED LABOUR IN HAZARA DIVISION - Nisa, Rahat -un-; Khattak, Khurshid A.; Bashir, Rubina; Parveen, Zahida (Journal of Ayub Medical College Abbottabad, 1999)
A very high incidence of obstructed labour in rural areas of our country in general and Hazara division in particular is a matter of great concern for us as obstetrician. Hence we embarked upon this study to evaluate factors leading to this grave complication, to explore the rote of health professionals at different levels in prevention and sometime causation and to rationalise treatment strategies. This retrospective study was performed between Jan 95 to June 98 to analyse the cases of obstructed labour in relation to the causes, presentations, morbidity, mortality and its prevention. There were 100 such cases. Total number of deliveries during this period was 4714 giving an incidence of I in 47 deliveries (2.12%). There were 22 cases of ruptured uterus with 2 maternal deaths and 51 perinatal deaths.